2016
DOI: 10.1364/optica.3.000377
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of excitons in individual InAs quantum dots revealed in four-wave mixing spectroscopy

Abstract: A detailed understanding of the population and coherence dynamics in optically driven individual emitters in solids and their signatures in ultrafast nonlinear-optical signals is of prime importance for their applications in future quantum and optical technologies. In a combined experimental and theoretical study on exciton complexes in single semiconductor quantum dots we reveal a detailed picture of the dynamics employing three-beam polarization-resolved fourwave mixing (FWM) micro-spectroscopy. The oscillat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 45 publications
4
65
0
Order By: Relevance
“…In the limit of ultrafast laser pulse excitation, in the range of τ ≈ 100 fs, we have shown that simulations in the delta-pulse limit yield a satisfactory agreement with experiments [38,46]. In this limit, the properties of the excited phonons only depend on the final occupation of the exciton state [47].…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…In the limit of ultrafast laser pulse excitation, in the range of τ ≈ 100 fs, we have shown that simulations in the delta-pulse limit yield a satisfactory agreement with experiments [38,46]. In this limit, the properties of the excited phonons only depend on the final occupation of the exciton state [47].…”
Section: Resultssupporting
confidence: 62%
“…S1(a)). A strong influence from the biexciton state would also lead to a beating for positive delays due to the biexciton binding energy [38]. Because the pulse spectrum has only little overlap with the exciton to biexciton transition, we do not resolve this beating for positive delays.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this context and the context of the single-photon amplifier, it is important to understand the intrinsic relaxation mechanisms which can influence preparation and readout of the few-particle quantum states via ultrashort light pulses. To this end, charge-carrier dynamics in QDs based on III-V semiconductors with shallow quantum confinement has been studied both in large ensembles [18][19][20] and single specimens [7,[21][22][23][24][25][26]. These developments have culminated in demonstrations of optical writing and readout of spin states in single or coupled QDs [13][14][15][16][17]27].…”
Section: Introductionmentioning
confidence: 99%
“…TFWM and two-dimensional Fourier spectroscopy were used to investigate the coherent optical response of exciton polaritons in QW-and QDbased microcavities with high quality factors (strong coupling regime) [2,18,19]. QDs were also implemented in low quality DBR-based cavities in order to increase the strength of the TFWM signal and to study the corresponding coherent optical phenomena [20][21][22]. However, studies of the nonlinear optical response under resonant excitation in TP resonators is lacking.…”
mentioning
confidence: 99%